Architectural Story of Jordan - Qusai muhammed alkhawaldeh - Esra akbalik, (Journal of engineering sciences and information technology, 2018)
Urban areas have always been rich scenes since they embody too much diversity and dynamics in both physical and social means for various disciplines. In the current era that we are living in, the criticality of urban areas has become more important with its rapidly increasing population and problems globally. This paper seeks to address an overview of the historical and architectural background of the evolution and improvement of Jordan architecture, by looking at its interaction with other civilizations that have passed on Jordan. In order to understand and comparison tendencies, it is necessary to see some projects in Jordan which compose the examples and evaluation part of the paper. The results for the selected projects confirmed two different types of relations which the Jordanian architects used to confirm the communication with heritage resources as imitation and Inspiration.